2003
DOI: 10.1136/adc.88.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilation in infants with malacia or recurrent wheeze

Abstract: Background: Controversy remains regarding the effectiveness of bronchodilators in wheezy infants. Aims: To assess the effect of inhaled β 2 agonists on lung function in infants with malacia or recurrent wheeze, and to determine whether a negative effect of β 2 agonists on forced expiratory flow (V′ maxFRC ) is more pronounced in infants with airway malacia, compared to infants with wheeze. Methods: We retrospectively analysed lung function data of 27 infants: eight with malacia, 19 with recurrent wheeze. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Double-blind placebo-controlled studies have demonstrated significant bronchodilatory effects [95][96][97][98] and protective effects against bronchoconstrictor agents [99,100] in infants and preschool children treated with rapidly acting inhaled b 2 -agonist. Thus, infants possess functional b 2 -receptors from birth, and stimulation of these receptors can produce the same effects as in older children, although paradoxical responses to inhaled b 2 -agonists have been reported in infants [50,101]. Oral administration of b 2 -agonist is also effective but is limited by systemic side-effects [102].…”
Section: Pharmacological Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Double-blind placebo-controlled studies have demonstrated significant bronchodilatory effects [95][96][97][98] and protective effects against bronchoconstrictor agents [99,100] in infants and preschool children treated with rapidly acting inhaled b 2 -agonist. Thus, infants possess functional b 2 -receptors from birth, and stimulation of these receptors can produce the same effects as in older children, although paradoxical responses to inhaled b 2 -agonists have been reported in infants [50,101]. Oral administration of b 2 -agonist is also effective but is limited by systemic side-effects [102].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Noisy breathing is common among infants aged ,6 months but only a small proportion have wheeze [15]. Reported noisy breathing that responds to bronchodilator therapy is likely to be genuine wheeze and to be caused, at least in part, by constriction of airway smooth muscle [50].…”
Section: History and Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Вопреки распро-страненному мнению о низкой чувствительности детей раннего возраста к этим препаратам, доказано, что у младенцев с рождения имеются функциониру-ющие β 2 -адренорецетроры и их стимуляция приво-дит к такому же клиническому эффекту, как и у детей более старшего возраста. Однако у некоторых мла-денцев (возможно, с дистонией бронхов или при не-обратимой обструкции) на препараты этой группы возникает парадоксальный терапевтический эффект [15]. Назначение короткодействующих β 2 -агонистов per os не рекомендуется из-за медленного начала дей-ствия и более выраженных, чем при ингаляционном введении, системных нежелательных эффектов [16].…”
Section: оригинальные статьи пульмонологияunclassified
“…Difficulties in defining phenotypes and objective outcome parameters combined with the transient nature of symptoms which often resolve spontaneously have confounded many studies [14]. Some studies showed a beneficial effect of short-acting b 2 -receptor agonists on lung function and clinical parameters [15][16][17], some did not show any effect [18][19][20][21], or even worsening of Asthma therapy for children Boehmer and Merkus 35 [22][23][24]. A meta-analysis concluded that there is no clear evidence to support the use of b 2 -receptor agonists for recurrent wheeze in children under 2 years old [14].…”
Section: Preventive Measuresmentioning
confidence: 99%